Sedimentary processes controlling gas hydrate accumulation in the Shenhu area of the northern South China Sea - Wenlin Chen; Wenlin Chen; Chenyang Bai; Chenyang Bai; Chenyang Bai; Hongyuan Xu; Hongyuan Xu; Xiaolei Xu; Xiaolei Xu (Frontiers in Marine Science)
Gas hydrates, as an environmentally friendly energy resource, are primarily distributed in marine sediments, with the vast majority occurring in subseafloor fine-grained sediments. However, the formation mechanisms of gas hydrates within fine-grained sediments remain poorly constrained. In addition to the temperature and pressure conditions, variations in sedimentary layer properties resulting from distinct sedimentary processes critically control gas hydrate accumulation. Since the Quaternary, substantial environmental and sedimentary dynamic changes in the northern South China Sea have likely influenced gas hydrate enrichment. This paper investigates the variability of sedimentary processes and its implications for gas hydrate accumulation by integrating analyses of sediment grain-size parameters, clay mineral characteristics, biological data, and geochemical data. The results indicated that the gas hydrate reservoir in the study area was predominantly bearing in fine-grained turbidite sediments. In contrast, the overlying hydrate-free layer is primarily influenced by traction flow dynamics, specifically contour currents. The differences in the sedimentary processes are mainly governed by sea-level fluctuations and climate variations, which modulate the hydrodynamic intensity and sediment provenance. During periods of low sea level and colder climate conditions, gravity flows preferentially develop fine-grained turbidite deposits. Sediments form in such sedimentological and environmental conditions promote gas hydrate accumulation. Conversely, during periods of high sea level and warmer climate conditions, the enhanced contour current intensity and velocity are accompanied by increased illite/smectite mixed-layer content, whose complex internal structure and large specific surface area reduce sediment porosity and permeability, thereby inhibiting gas hydrate formation. These findings not only reveal the coupling between sedimentary processes and gas hydrate enrichment but also elucidate the underlying mechanisms driving this relationship. Moreover, they establish a link between paleoclimate conditions and gas hydrate enrichment by positioning sedimentary processes as an intermediary. This study contributes significantly to the understanding of gas hydrate accumulation theory and its environmental implications.